Avaliação experimental da influência da viscosidade da fase líquida no escoamento bifásico líquido-gás em golfadas em tubulações horizontais - Naidek, Bruna Patricia (2020)
Two-phase slug flow is present in various industrial processes, especially in the oil industry with the production of oil in deep water. Slug flow is characterized by the intermittent succession of liquid slugs, which have a large momentum, that may contain bubbles of compressible gas, followed by elongated bubbles of gas occupying much of the cross-section of the pipeline. Few studies are found in the literature that seek to evaluate the effect of viscosity in this flow pattern. Among the studies found, the majority evaluate liquid viscosities considered high (above 100 cP). In this work, the influence of the liquid viscosity considered average (1 to 30 cP) on the characteristic flow parameters is evaluated. To achieve the proposed objective, experiments were carried out on the NUEM/UTFPR horizontal experimental circuit. The fluids used were air, water and mixtures of water with glycerin to obtain all the desired viscosities. The detection of the phases was performed using resistive sensors, installed in four sections of the pipe, in addition to a camera with a high rate of image acquisition to visualize the flow. From the acquired signals, the average values and statistical distributions of the characteristic parameters of the slug flow were extracted, such as the bubble velocity, slug and bubble lengths and frequency. After a careful analysis of the experimental data, the influence of viscosity on the slug flow structures was correlated. Among the effects of the viscosity of the liquid phase are the increase in the bubble velocity and the slug frequency and the reduction in the length of the unit cell. Correlations were developed to calculate the average characteristic parameters of the slug flow from the flow operating conditions such as surface velocity and fluid properties. The experimental data and correlations of this study can be used as database and to validation of slug flow models in horizontal pipes.